Go contributes to olfactory reception in Drosophila melanogaster. - Chatterjee, A.; Roman, G.; Hardin, P.E. (BMC physiology, 2009)
Seven-transmembrane receptors typically mediate olfactory signal transduction by coupling to G-proteins. Although insect odorant receptors have seven transmembrane domains like G-protein coupled receptors, they have an inverted membrane topology and function as ligand-gated cation channels. Consequently, the involvement of cyclic nucleotides and G proteins in insect odor reception is controversial. Since the heterotrimeric Goalpha subunit is expressed in Drosophila olfactory receptor neurons, we reasoned that Go acts together with insect odorant receptor cation channels to mediate odor-induced physiological responses.To test whether Go dependent signaling is involved in mediating olfactory responses in Drosophila, we analyzed electroantennogram and single-sensillum recording from flies that conditionally express pertussis toxin, a specific inhibitor of Go in Drosophila. Pertussis toxin expression in olfactory receptor neurons reversibly reduced the amplitude and hastened the termination of electroantennogram responses induced by ethyl acetate. The frequency of odor-induced spike firing from individual sensory neurons was also reduced by pertussis toxin. These results demonstrate that Go signaling is involved in increasing sensitivity of olfactory physiology in Drosophila. The effect of pertussis toxin was independent of odorant identity and intensity, indicating a generalized involvement of Go in olfactory reception.These results demonstrate that Go is required for maximal physiological responses to multiple odorants in Drosophila, and suggest that OR channel function and G-protein signaling are required for optimal physiological responses to odors.